Sistema informatizado para rastreabilidade na produção de sementes - Marcolin, Lucas (2011)
The growing demand of consumer markets for seed quality and safety to the producer and consumer is ordering from the production sector a continuous adaptation. Food safety has become an important attribute of food quality. The traceability is in line with this view, since it integrates the entire production chain in a monitoring and certification system. Traceability programs for the productive chain are essential for logistics and management of seed production. The aim of this study was to develop and validate an efficient and effective traceability system for seed production, through a scheme of software, in order to ensure the quality and safety of the products obtained, as well as an important management tool, making the productive chain more competitive in the market. In addition to an extensive literature review, it was also made a partnership with the company Checkplant Traceability Systems LTD, in order to assist in the software scheme that they have already developed for fruit producers and many others. Furthermore, interviews with companies, researchers and seed producers from the south region helped to collect necessary data for the proposed software and to understand the obstacles and critical points of the productive chain. It was presented and tested with the users, the system screens which can work for them, containing the field part (record of field activities, its settings and reports) and the post-harvest stage (record of the activities in the Seed Processing Unit, reports, etc.), paying attention to what should be enhanced to the system implementation. It was observed that the proposed system, based on what happens with fruit producers, it is perfectly adaptable and feasible for seed producers, ensuring, besides of traceability, an important management tool